Mapping the path to sustainability through coherence analysis of Colombia’s land, food, and water policies - Buritica, Alexander; Howland, Fanny Cecile; Mideros, Maria Fernanda; Castro Nunez, Augusto (2024)
The intricate interconnections between food, land, and water systems are fundamental to societal sustainability, necessitating coherent policies that address these critical domains. The CGIAR's National Policies and Strategies (NPS) for the Transformation of Food, Land, and Water Systems Initiative, launched in 2021, focuses on enhancing policy coherence in six pilot countries, including Colombia. This policy brief analyzes Colombia’s land, food, and water policies, examining their alignment with the Sustainable Development Goals (SDGs) and the CGIAR impact areas. The study assesses how these policies contribute to objectives such as poverty reduction, food security, health, gender equality, climate action, and land conservation. The findings reveal the current state of policy alignment and offer recommendations to strengthen cross-sectoral synergies, ultimately aiming to achieve more sustainable and equitable development outcomes.